EFFECT OF DIFFERENT DOSES OF NITROGEN ON ECONOMICAL YIELD AND PHYSIO-CHEMICAL CHARACTERISTICS OF APPLE FRUITS - M. Iqbal; M. Niamatullah; D. Mohammad (Journal of Animal and Plant Sciences, 2012)
The experiment was conducted at Horticulture Research Area, Fort Munroo, District D.G. Khan during 2008 with an objective to observe the effects of different doses of nitrogen fertilizer on economical yield and physio-chemical composition of apple (red delicious). The field experiment was laid down in Randomized Complete Block Design having one control, four levels of nitrogen @500, 600, 700, 800 grams per tree and three replications. The parameters under study were comprised of fruit weight (gm), size of fruit (cm), pulp weight (gm), economical yield per tree (kg) along with chemical characteristics of fruits such as pH, acidity (%) and total soluble solids (TSS). The results of the study revealed that fruit yield /tree (kg) have been influenced by application of nitrogen treatment T5 (800 gm N/ tree) significantly in Fort Munroo region of District D.G. Khan.
Keywords: Yield; Nitrogen; Pulp; Fertilizer; Fruit size; D.G. Khan.